Sex-dependent effects on tasks assessing reinforcement learning and interference inhibition - Evans, Kelly L.; Hampson, Elizabeth (Frontiers in Psychology, 2015)
Increasing evidence suggests that the prefrontal cortex (PFC) is influenced by sex steroids and that some cognitive functions dependent on the PFC may be sexually differentiated in humans. Past work has identified a male advantage on certain complex reinforcement learning tasks, but it is unclear which latent task components are important to elicit the sex difference. The objective of the current study was to investigate whether there are sex differences on measures of response inhibition and valenced feedback processing, elements that are shared by previously studied reinforcement learning tasks. Healthy young adults (90 males, 86 females) matched in general intelligence completed the Probabilistic Selection Task (PST), a Simon task, and the Stop-Signal task. On the PST, females were more accurate than males in learning from positive (but not negative) feedback. On the Simon task, males were faster than females, especially in the face of incongruent stimuli. No sex difference was observed in Stop-Signal reaction time. The current findings provide preliminary support for a sex difference in the processing of valenced feedback and in interference inhibition.